A Study of Ecology and Phytogeography Characteristics in Plants Flora: Exploring the Ecological and Phytogeographical Characteristics of Plant Flora in Namibia (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Plants Of Namibia Have Been Mapped In Several Ways Using Different Criteria. This Paper Categorieses These Maps According To Different Approaches To Phytogeography. A Summary And Analysis Of These Diverse Methods, Their Scientific Merit And Usefulness Of Each In Terms Of Defining The Geographic Patterns Of Plants In Namibia Is Given. In Addition, Abiotic Aspects, E.G. The Palaeoenvironment, And Pollen Studies Relevant To Historical Phytogeography, Are Discussed. Phytogeography of the Pasturage Community of Almoguera. Climatephilous ligneous developments on not-gypsiferous soils. It utilizes field work and bibliographic and cartographic documentation to do the Phjrtogeography of a Southern Alcarria Sector (Pasturage Community of Almoguera). The examination is a surveillance overview concurring a coordinated technique a concurrent methodology among topographical and phytosociological sees is actualized in the vegetation consider. It decides climatephilous ligneous arrangements on not-gypseous soils forests of Quercus rotundifolia and Q. faginea. In light of a review completed in the southern Yukon (Canada), an expansive, phytogeographically fascinating district whose vegetation was somewhat inadequately known, the paper incorporates an order of the vegetation into network types, their ecological portrayal based on direct information, and a phytogeographic examination dependent on the world scopes of all important vascular plant species. Multivariate methods of characterization and appointment were utilized in broad vegetational, ecological and phytogeographic facilitated examinations to think about the connection between's some major ecological factors and the frequencies inside networks of species with comparative world conveyance.